Contemporary Learning Theories and Their Implications for Islamic Education: A Critical Study of Kegan, Mezirow, and John Dewey - Muhamad Ikhsanudin; Sholeh Hasan; Kasinyo Harto; Mardiah Astuti (FKIP - Universitas Riau, 2026)
Contemporary learning theories offer valuable insights for enhancing Islamic education by emphasizing reflection, experience, and personal development. This study aims to systematically analyze and critically compare the learning theories of Robert Kegan, Jack Mezirow, and John Dewey, focusing on their conceptual foundations and practical implications for the development of Islamic education. This research employs a systematic literature review method by analyzing primary and secondary scholarly sources through content analysis, comparative analysis, and critical-reflective interpretation. Findings reveal that all three theories share a transformative orientation, emphasizing active learning, reflection, and holistic development encompassing cognitive, affective, social, and spiritual dimensions. Integrating these theories into Islamic education can enhance curriculum design, learning methods, prevent radicalism, and promote lifelong learning aligned with Islamic principles. The study concludes that contemporary learning theories provide a strong conceptual foundation for developing an Islamic education system that is reflective, adaptive, and relevant to modern societal challenges.